Køns betydning for lokalaftaler om ligeløn og familie-arbejdsliv - Trine P. larsen (The Royal Danish Library, 2012)
This paper explores to what extent the government and social partners’ recent work-life balance and equal pay initiatives are discussed and negotiated in Danish workplaces. It argues that whilst work-life balance issues often are at the top of social partners’ bargaining agenda at company level, equal pay typically figures at the very bottom. In addition, these issues are more likely to be up for local bargaining in companies where women constitute one in two or more of the employees – and in such companies it is interestingly often the male shop steward who takes the lead.